2020
DOI: 10.1186/s13148-020-00967-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic profiling of Italian patients identified methylation sites associated with hereditary transthyretin amyloidosis

Abstract: Hereditary transthyretin (TTR) amyloidosis (hATTR) is a rare life-threatening disorder caused by amyloidogenic coding mutations located in TTR gene. To understand the high phenotypic variability observed among carriers of TTR disease-causing mutations, we conducted an epigenome-wide association study (EWAS) assessing more than 700,000 methylation sites and testing epigenetic difference of TTR coding mutation carriers vs. non-carriers. We observed a significant methylation change at cg09097335 site located in B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Broad intra and interfamilial variations in terms of age of onset and severity have been observed in ATTRv amyloidosis, caused by diverse mutations. Therefore, we can speculate that genetic modifiers and epigenetic factors are causing such variability (21,22). Future research should be conducted to reach more definitive conclusions.…”
Section: Discussionmentioning
confidence: 93%
“…Broad intra and interfamilial variations in terms of age of onset and severity have been observed in ATTRv amyloidosis, caused by diverse mutations. Therefore, we can speculate that genetic modifiers and epigenetic factors are causing such variability (21,22). Future research should be conducted to reach more definitive conclusions.…”
Section: Discussionmentioning
confidence: 93%
“…4 F ). In addition, TTR and a second gene B4GALT6 , which are also strongly linked to amyloidosis in mice and human ( 21 , 22 ), are located in the ROH region of the BFC. Moreover, a missense deleterious mutation (alanine to glycine) on the 37th amino acid site of another gene related to amyloidosis ( BACE1 ) was found in the BFC.…”
Section: Resultsmentioning
confidence: 99%
“…Variability in phenotype and penetrance of ATTRv amyloidosis can conceivably be explained by epigenetic modifications especially when we consider monozygotic twins that carry the same variant yet display different clinical presentations [59][60][61][62] In an epigenome-wide association study (EWAS) on 48 carriers (38 symptomatic and 10 asymptomatic) of TTR variants Val30Met, Phe64Leu, Ala120Ser, Ile68Leu, and Val122Ile and 32 controls, it was found that a CpG site in the Beta-secretase 2 (BACE2) gene was significantly hypomethylated in variant carriers [123]. BACE2 is known for cleaving APP in the brain, but is also present in peripheral tissues in inflammatory responses leading to the hypothesis that there might be a link between BACE2 and TTR-induced inflammation.…”
Section: Epigenetic and Environmental Factorsmentioning
confidence: 99%